2023
DOI: 10.1177/07067437231158933
|View full text |Cite
|
Sign up to set email alerts
|

Amphetamine-Related Emergency Department Visits in Ontario, Canada, 2003-2020

Abstract: Objectives Despite unregulated amphetamine use increasing, there are limited data on related emergency department (ED) visits in Canada. Our primary objective was to examine trends in amphetamine-related ED visits over time in Ontario, including by age and sex. Secondary objectives were to examine whether patient characteristics were associated with ED revisit within 6 months. Methods Using administrative claims and census data, we calculated annual patient- and encounter-based rates of amphetamine-related ED … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…In British Columbia, the presence of methamphetamine in drug toxicity-related deaths increased from 20.7% in 2012 to 43% in 2022 ( 6 ), and methamphetamine was involved in 52% of apparent stimulant toxicity deaths across Canada between January and September 2022 ( 7 ). In Ontario, there was an increase of more than 200% in population-based emergency department visits related to amphetamines between 2015 and 2020 ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…In British Columbia, the presence of methamphetamine in drug toxicity-related deaths increased from 20.7% in 2012 to 43% in 2022 ( 6 ), and methamphetamine was involved in 52% of apparent stimulant toxicity deaths across Canada between January and September 2022 ( 7 ). In Ontario, there was an increase of more than 200% in population-based emergency department visits related to amphetamines between 2015 and 2020 ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Spinal cord injuries (SCIs), the leading cause of irreversible paralysis, have a profound and devastating impact on the lives of more than 20 million people worldwide due to the limited capability to regenerate or replace neuronal tissue. 1 Previous studies in the field of neurobiology revealed that the deficiency of neuronal regeneration in the central nervous system (CNS) is not only because of the intrinsic lack of CNS axon regeneration ability but also because of extrinsic cell growth inhibition signals conferred by the CNS environment within the damaged tissue. 2 Thus, if neurons are provided with the correct set of biological and physical stimuli, regeneration of the damaged neuronal tissue should be favored.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, an ever-growing prevalence of people who use amphetamine-type stimulants (ATS) has been reported in various regions of the world [1][2][3]. According to the World Drug Report 2022, 34 million people used amphetamines in the year 2020 alone [2].…”
Section: Introductionmentioning
confidence: 99%